The challenge: educate to coexist - Montaña Beltrán, Andrea Carolina; Rocha Adame, Zulma Carmenza; Rojas Hernández, Ana Milena (Universidad Pedagógica y Tecnológica de Colombia, 2019)
Educating to coexist is the challenge assumed by today’s teachers to work in the construction of a peaceful society. This research aimed to developpedagogical strategies that promote school coexistence in the third, fourth and fifth grade students of the branch “Campoamor” of the “ÁlvaroGonzález Santana” Educational Institution (IEPAGS), in Sogamoso - Boyacá. school life, communicative citizenship skills (CCC), and classroom climate: three axes that gave meaning to the research were defined. Likewise, pedagogical strategies proposed from Guide 49 “Pedagogical guidelines for school coexistence” of the Ministry of National Education - MEN, aimed at the development of communicative citizenship skills: argumentation, assertiveness and active listening. Based on the results, an evaluation was made through the analysis of this implementation that led to the construction of recommendationsaddressed to the IEPAGS to strengthen school coexistence.